Clinical symptoms of colorectal cancer – a retrospective study - Banaszkiewicz, Zbigniew; Tojek, Krzysztof; Jarmocik, Paweł; Frasz, Jacek; Jawień, Arkadiusz (Contemporary Oncology/Współczesna Onkologia, 2009)
Even though the clinical manifestation of colorectal cancer (CRC) appears rather late, still a large portion of CRCs including those in an early stage of the disease are symptomatic ones. Thus it seems crucial to know how to examine patients and to educate people what symptoms to be aware of. The aim of the present study was a retrospective, multivariable analysis of symptoms present in CRC patients in relation to age, sex, CRC staging and tumour localisation. Medical records of 453 consecutive patients treated for CRC in the Department of General Surgery in the years 1994-2001 were analysed to match the clinical symptoms with both patient and tumour related variables. 379 out of them were recognised as symptomatic ones. The most frequent symptoms were overt rectal bleeding (51.45%) and bowel movement disturbance such as constipation (25.33%) and diarrhoea (21.11%). Rectal bleeding, anaemia and body mass loss were all statistically more frequent in older patients. Abdominal pain, diarrhoea and significant body mass loss correlated strongly with CRC staging. It was tumour location that had the greatest impact on clinical symptoms in CRC patients.